Modulation of Photorespiratory Enzymes by Oxidative and Photo-Oxidative Stress Induced by Menadione in Leaves of Pea (Pisum sativum) - Ramesh B. Bapatla; Deepak Saini; Vetcha Aswani; Pidakala Rajsheel; Bobba Sunil; Stefan Timm; Agepati S. Raghavendra (Plants, 2021)
Photorespiration, an essential component of plant metabolism, is concerted across four subcellular compartments, namely, chloroplast, peroxisome, mitochondrion, and the cytoplasm. It is unclear how the pathway located in different subcellular compartments respond to stress occurring exclusively in one of those. We attempted to assess the inter-organelle interaction during the photorespiratory pathway. For that purpose, we induced oxidative stress by menadione (MD) in mitochondria and photo-oxidative stress (high light) in chloroplasts. Subsequently, we examined the changes in selected photorespiratory enzymes, known to be located in other subcellular compartments. The presence of MD upregulated the transcript and protein levels of five chosen photorespiratory enzymes in both normal and high light. Peroxisomal glycolate oxidase and catalase activities increased by 50% and 25%, respectively, while chloroplastic glycerate kinase and phosphoglycolate phosphatase increased by ~30%. The effect of MD was maximum in high light, indicating photo-oxidative stress was an influential factor to regulate photorespiration. Oxidative stress created in mitochondria caused a coordinative upregulation of photorespiration in other organelles. We provided evidence that reactive oxygen species are important signals for inter-organelle communication during photorespiration. Thus, MD can be a valuable tool to modulate the redox state in plant cells to study the metabolic consequences across membranes.